Persephin as a diagnostic marker of acute brain injury in critically ill newborns: a clinical trial - A. A. Zadvornov; E. V. Grigoriev (Фундаментальная и клиническая медицина, 2021)
Aim. To study the correlation of serum persephin with clinical, instrumental and biochemical indicators of brain damage and with an adverse outcome in critically ill newborns.Materials and Methods. The study included 44 critically ill newborns. Blood samples were collected on the 1st and 7th day of life. Brain injury was assessed by recording Apgar score, depression of consciousness and brainstem reflexes in unsedated patients over 7 days of life, convulsions, neurosonographic signs of cerebral edema, serum protein S100B on the 1st and 7th day of life, and using indicators of adverse neurological outcome. The correlation of serum persephin on the 1st and 7th day of life with signs of brain damage was evaluated using the Spearman's rank correlation coefficient and Mann-Whitney U-test.Results. No statistically significant correlation was found between the concentrations of serum persephin on the 1st and 7th day of life and Apgar score (p = 0.721 and 0.222, respectively), depression of consciousness and stem reflexes (p < 0.05), convulsions (p = 0.673 and 0.432, respectively), cerebral edema (p = 0.737 and 0.558, respectively), and serum protein S100B both on the 1st day (p = 0.095 and 0.475, respectively) and 7th day of life (p = 0.988 and p = 0.775, respectively). Further, there was no statistically significant association of the serum persephin on the 1st day of line with an unfavorable outcome (p = 0.294). Yet, we revealed an association of serum persephin on the 7th day of life with an unfavorable outcome (p = 0.013), with a cut-off point of 828 ng/mL, a sensitivity of 39%, and a specificity of 100%.Conclusion. Persephin has poor diagnostic and prognostic significance for assessing the severity of brain damage in critically ill newborns. The obtained data on the correlation of the concentration of persephin for 7 days with an unfavorable outcome are doubtful due to the lack of data on its correlation with signs of severe brain damage.